Fungsi Pengawasan Bank oleh Otoritas Jasa Keuangan dalam Penyaluran Kredit bagi Badan Usaha Milik Swasta - I Komang Arya Wisnu Amerta; Ni Komang Arini Satyawati; Desak Gde Dwi Arini (Fakultas Hukum Universitas Warmadewa, 2021)
This study was conducted to describe the function of bank supervision by the OJK in the delivery of credit for private-owned enterprises, the follow-up of banks by the Financial Services Authority in credit supervision for private-owned enterprises? The research was conducted legally normatively. Sources of primary legal materials from applicable laws and regulations such as Law No. 21/2011. Secondary sources of legal materials from literature. The research analysis was conducted qualitatively and the results were presented descriptively. The results of the research that the function of bank supervision by the OJK in the delivery of credit for Private Owned Enterprises (BUMS) is following Article 6 of Law Number 21/2011 that bank supervision is carried out to encourage banks to consistently implement banking regulations and refer to the principle of prudence. As a follow- up to OJK's supervision in lending to BUMS, if there are difficulties or credit, OJK cooperates with Bank Indonesia as the Lender of Last Resort to overcome the problem of difficulties in maintaining banking security and ensuring the safety of customers as consumers.